Full-recycled concrete as well as preparation method and application thereof

By optimizing the slurry and bone ratio and water-cement ratio, using a secondary stirring process, and introducing water-based polyurethane-epoxy resin emulsion and nanoclay composite materials as reinforced toughening agents, the problem of insufficient mechanical properties and durability in the existing regenerated concrete technology is solved, and the compressive strength, chloride ion permeability and frost resistance of fully regenerated concrete are significantly improved.

CN119569399AActive Publication Date: 2025-03-07ZHEJIANG COMM CONSTR GRP CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510138021.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-07
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The existing recycled concrete technology is difficult to effectively utilize brick-concrete construction solid waste, and its mechanical properties and durability are insufficient, especially in terms of anti-chlorine ion penetration and frost resistance.

Method used

By optimizing the slurry and bone ratio and water-cement ratio, a secondary stirring process is adopted, and aqueous polyurethane-epoxy resin emulsion and nanoclay composite are introduced as reinforcement toughening agents, and the mechanical properties and durability of fully recycled concrete are used together to improve the mechanical properties and durability of fully recycled concrete.

Benefits of technology

The compressive strength, split tensile strength, chloride ion permeability and freezing resistance of fully recycled concrete have been significantly improved, making its freezing life in North China reach 20-30 years and its durability performance significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses all-recycled concrete as well as a preparation method and application thereof. The all-recycled concrete provided by the invention is prepared from the following components in parts by weight: 290 to 540 parts of cement, 1100 to 1200 parts of brick-mixed recycled coarse aggregate, 650 to 680 parts of brick-mixed recycled fine aggregate, 145 to 250 parts of water, 30 to 80 parts of steel fiber, 1.4 to 2.7 parts of polycarboxylic acid high-performance water reducing agent and 40 to 60 parts of reinforcing and toughening agent. The reinforcing and toughening agent is prepared by mixing waterborne polyurethane-epoxy resin emulsion and a synergist according to the mass ratio of (2 to 4): 1. Compared with the prior art, the full-recycled concrete prepared by the preparation method disclosed by the invention has relatively good compressive strength, splitting tensile strength, axial compressive strength, chloride ion infiltration resistance and frost resistance, and has relatively long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete, and in particular to a fully recycled concrete and a preparation method and application thereof. Background Art

[0002] The survey results show that the recycling rate of construction solid waste is insufficient. How to scientifically and effectively utilize construction solid waste as a resource is an enduring research hotspot in the building materials industry. The engineering application of recycled concrete technology turns construction solid waste into treasure, which not only saves concrete raw materials, but also has social, economic and environmental benefits. The fully recycled concrete prepared by using recycled coarse and fine aggregates can not only alleviate the shortage of construction resources to the greatest extent, but also absorb construction solid waste to the greatest extent, which is in line with the concept of sustainable development and green development. However, most of the current research on recycled concrete focuses on the recycling and reuse of waste concrete, and its experience and conclusions are not applicable to construction solid waste mainly composed of brick-concrete structures. The reason is that brick-concrete recycled aggregates have higher porosity, crushing value and water absorption rate, as well as lower apparent density than recycled aggregates of waste concrete. Therefore, it is necessary to develop a fully recycled concrete with brick-concrete recycled aggregates as the main aggregate and excellent mechanical properties and durability.

[0003] CN111320438A discloses a green environmentally friendly concrete and its preparation method. The green environmentally friendly concrete provided by the invention includes the following components by weight: 180-220 parts of silicate cement; 170-180 parts of water; 740-760 parts of medium sand; 800-860 parts of crushed stone; 210-240 parts of recycled concrete waste; 70-80 parts of fly ash; 160-190 parts of mineral powder; 4-5 parts of water reducer; 2-3 parts of retarder; 8-12 parts of filling and strengthening material; 10-16 parts of diatomaceous earth; 25-35 parts of urea; 8-10 parts of soybean seed coat powder. The green environmentally friendly concrete in the invention has a slow carbonization rate in long-term application, and can maintain good and stable compressive strength as a whole, but its anti-permeability performance has not been improved.

[0004] CN118771823A discloses a coarse aggregate ultra-high performance concrete and its preparation method and application. The coarse aggregate ultra-high performance concrete of the invention comprises 600-1000 parts of cement, 100-300 parts of silica fume, 100-200 parts of mineral admixture, 10-50 parts of water reducer, 600-1000 parts of fine aggregate, 200-600 parts of coarse aggregate, 50-200 parts of steel fiber, and 100-200 parts of water. Although the concrete provided by the invention has good compressive strength, elastic modulus, first crack flexural tensile strength, flexural tensile strength and fracture toughness, its frost resistance is poor, which is not conducive to long-term use. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, the present invention provides a fully recycled concrete, which optimizes the mortar-to-aggregate ratio, the water-cement ratio and adopts a secondary mixing process, while introducing a reinforcing and toughening agent for synergistic use, so that the fully recycled concrete provided by the present invention has good compressive strength, splitting tensile strength, axial compressive strength, resistance to chloride ion penetration and frost resistance.

[0006] To achieve the above object, the present invention provides a method for preparing fully recycled concrete, which is characterized by comprising the following steps: Add the brick-concrete recycled coarse aggregate and the brick-concrete recycled fine aggregate into a mixer and mix and stir for 110-130 seconds, add cement and water accounting for 1 / 2 of the total mass of water, and continue to stir for 80-100 seconds; then add the remaining 1 / 2 of water and polycarboxylic acid high-performance water reducer, and continue to stir for 50-70 seconds; then evenly sprinkle the steel fiber, stir for 160-200 seconds, and discharge the material to prepare the fully recycled concrete; Alternatively, the brick-concrete recycled coarse aggregate and the brick-concrete recycled fine aggregate are added into a mixer and mixed for 110-130 seconds, cement, reinforcing and toughening agent and water accounting for 1 / 2 of the total mass of water are added, and the mixing is continued for 80-100 seconds; then the remaining 1 / 2 of the water and the polycarboxylic acid high-performance water-reducing agent are added, and the mixing is continued for 50-70 seconds; then the steel fiber is evenly sprinkled, stirred for 160-200 seconds, and the material is discharged to prepare the fully recycled concrete.

[0007] Preferably, the weight ratio of each raw material component is: 290-540 parts of cement, 1100-1200 parts of recycled coarse aggregate for brick-concrete, 650-680 parts of recycled fine aggregate for brick-concrete, 145-250 parts of water, 30-80 parts of steel fiber, 1.4-2.7 parts of polycarboxylic acid high-performance water reducer; Or, 290-540 parts of cement, 1100-1200 parts of brick-concrete recycled coarse aggregate, 650-680 parts of brick-concrete recycled fine aggregate, 145-250 parts of water, 30-80 parts of steel fiber, 1.4-2.7 parts of polycarboxylic acid high-performance water reducing agent, and 40-60 parts of reinforcing and toughening agent.

[0008] Preferably, the steel fiber is selected from one of corrugated steel fiber and end hook steel fiber.

[0009] Preferably, the reinforcing and toughening agent is prepared by mixing a waterborne polyurethane-epoxy resin emulsion and a synergist in a mass ratio of 2-4:1.

[0010] In the present invention, the waterborne polyurethane-epoxy resin emulsion has a good effect on improving the strength of concrete. It can form a network structure inside the concrete, fill the pores, enhance the bonding force between aggregate and cement stone, and improve the overall compressive strength. The polyurethane in the waterborne polyurethane-epoxy resin emulsion is flexible and elastic, and can disperse stress, thereby improving the splitting tensile strength. And the polymer in the emulsion can enhance the concrete microstructure, and the toughening effect of the polyurethane can jointly improve the axial tensile strength of the concrete. In addition, the waterborne polyurethane-epoxy resin emulsion also has a good effect on improving the concrete's impermeability durability and freeze-thaw resistance. It can greatly enhance the concrete's ability to resist chloride ion penetration. After the emulsion forms a film, it fills the pores, reduces the porosity and pore size, and effectively blocks the migration and diffusion of chloride ions. And during the freeze-thaw cycle, the polymer in the emulsion can relieve internal stress concentration and reduce microcracks; at the microscopic level, it optimizes the concrete pore structure, reduces the freezable water content, reduces freeze-thaw damage, and maintains the integrity of the concrete.

[0011] Preferably, the preparation method of the synergist comprises the following steps, measured by weight: S1, 1.5-3 parts by weight of eucommia gum and 95-105 parts by weight of toluene are mixed and stirred until the eucommia gum is dissolved, and then 0.3-0.4 parts by weight of hydrogen peroxide and 0.1-0.2 parts by weight of formic acid are added, and the mixture is reacted at 38-42° C. for 4-6 hours to obtain a mixed solution; then 8-12 parts by weight of water are added to the mixed solution, and the mixture is stirred for 0.5-2 hours to obtain an epoxidized eucommia gum latex; 8-12 parts by weight of nanoclay are mixed and stirred with 95-105 parts by weight of water to obtain a suspension, and the suspension is added to the above-mentioned epoxidized eucommia gum latex, and the reaction is stirred for 0.5-2 hours, and the product is precipitated with anhydrous ethanol, washed, and dried in vacuo at room temperature to obtain modified nanoclay; S2. Mix 1.5-3 parts of the modified nanoclay prepared in the above step S1, 25-35 parts of anhydrous ethanol and 0.01-0.1 parts of phytic acid, and stir at 300-500 rpm and 75-85° C. for 3-5 hours to obtain a mixed solution; centrifuge the mixed solution, collect the precipitate, wash it with water, and then vacuum dry it at 55-65° C. to obtain a nanoclay composite material, i.e., a synergist.

[0012] Preferably, the step S2 may also be, by weight: 1.5-3 parts of the modified nanoclay prepared in the above step S1, 25-35 parts of anhydrous ethanol, 0.01-0.1 parts of phytic acid and 0.01-0.05 parts of a corrosion inhibitor are mixed, and the mixture is stirred at 300-500 rpm and 75-85° C. for 3-5 hours to obtain a mixed solution; the mixed solution is centrifuged, the precipitate is collected, and the precipitate is washed with water and vacuum dried at 55-65° C. to obtain a nanoclay composite material, i.e., a synergist.

[0013] Further preferably, the corrosion inhibitor is selected from at least one of zinc chloride and cerous nitrate hexahydrate.

[0014] Nanoclay, as a nano-enhancer, can fill the pores of concrete, enhance the bonding force between aggregate and cement stone, and optimize the microstructure of concrete, thereby improving the overall uniform density and strength of concrete. Concrete with nanoclay added has lower porosity and pore size, making it more difficult for chloride ions to migrate and diffuse inside the concrete, and the resistance to chloride ion penetration is significantly improved. In addition, during the freeze-thaw cycle, nanoclay can alleviate the stress concentration inside the concrete, reduce the microcracks caused by freeze-thaw action, and maintain the integrity of the concrete. However, since nanoclay is easy to form agglomeration in concrete and has poor compatibility with waterborne polyurethane-epoxy resin emulsion, it will reduce the uniformity of nanoclay in the concrete matrix, resulting in local stress concentration, while affecting the rheological properties and workability of concrete, not only affecting the overall performance of concrete, but also increasing the difficulty of concrete construction. Based on this, the nanoclay composite material prepared by the present invention is mixed with the waterborne polyurethane-epoxy resin emulsion as a reinforcing and toughening agent for the fully recycled concrete of the present invention, which can effectively solve the problem of easy agglomeration of nanoclay in concrete, and improve the problem of poor compatibility between nanoclay and waterborne polyurethane-epoxy resin emulsion, and further improve the compressive strength, splitting tensile strength, chloride ion penetration resistance and frost resistance of the brick-concrete aggregate fully recycled concrete of the present invention.

[0015] As for the preparation method of the above-mentioned synergist, the present invention firstly subjectes eucommia gum to epoxidation reaction under the action of hydrogen peroxide and formic acid to obtain epoxidized eucommia gum latex, and then mixes it with nanoclay. The epoxy groups introduced in the epoxidized eucommia gum latex react with the hydroxyl groups on the surface of the nanoclay to epoxy-ring-opening reaction and are grafted to the surface of the nanoclay to prepare epoxidized eucommia gum modified nanoclay, which improves the surface activity of the nanoclay and introduces epoxy groups; then the modified nanoclay is mixed with phytic acid and a corrosion inhibitor for reaction, and the phytic acid contains multiple phosphate groups, which can react with the epoxy groups introduced by the epoxidized eucommia gum to form a strong chemical bond, thereby grafting the phytic acid to the surface of the modified nanoclay; then the corrosion inhibitor ions zinc ions or cerium ions in the corrosion inhibitor can react with the phosphate groups in the phytic acid grafted on the surface of the nanoclay to form a stable coordination compound, which is fixed to the surface of the nanoclay, thereby preparing a nanoclay composite material, that is, the synergist of the present invention.

[0016] The present invention also provides a fully recycled concrete prepared by the above method.

[0017] The present invention also provides application of the fully recycled concrete in bridges, roads and high-rise buildings.

[0018] In the present invention, steel fiber has the effect of toughening and resisting cracking, while concrete is a typical brittle material. When an appropriate amount of steel fiber is added to the fully recycled concrete, the steel fiber can enhance the durability of the fully recycled concrete by improving the pore structure and the interface transition zone, and give full play to its bridging effect, which can effectively improve the defects of low tensile strength, high brittleness and easy cracking of concrete, and has a significant enhancing effect on the overall performance of the fully recycled concrete.

[0019] Beneficial effects of the present invention: 1. Compared with the prior art, this paper uses 100% of brick-concrete recycled coarse and fine aggregates to replace natural aggregates, configures brick-concrete aggregate fully recycled concrete, and adds steel fiber to the fully recycled brick-concrete aggregate concrete, providing a reference for the efficient use of brick-concrete construction solid waste; at the same time, by optimizing the mortar-brick ratio, water-cement ratio and adopting a secondary mixing process, the brick-concrete construction solid waste is high-valued and fully utilized, providing support for expanding the practical engineering application of fully recycled concrete. The fully recycled concrete provided by the present invention not only has excellent mechanical properties and toughness, but also has good resistance to chloride ion penetration and frost resistance. The frost resistance life in North China is between 20-30 years, and the durability is good.

[0020] 2. Compared with the prior art, the present invention prepares a nanoclay composite material by composite modification of nanoclay, and mixes it with waterborne polyurethane-epoxy resin emulsion as a synergist as a reinforcing and toughening agent for the fully recycled concrete of the present invention, which can effectively solve the problem of easy agglomeration of nanoclay in concrete, and improve the problem of poor compatibility between nanoclay and waterborne polyurethane-epoxy resin emulsion, further improve the compressive strength, splitting tensile strength, chloride ion penetration resistance and frost resistance of the brick-concrete aggregate fully recycled concrete of the present invention, which is conducive to further improving the durability of the fully recycled concrete. DETAILED DESCRIPTION

[0021] The parameters and sources of specific chemical substances used are as follows: Brick-concrete recycled coarse aggregate is a recycled building material. It mainly comes from construction waste after the demolition of abandoned brick-concrete structure buildings. Through a series of processing such as crushing and screening, abandoned bricks, a small amount of concrete blocks and other components are made into granular materials with a particle size greater than 4.75mm. These granular materials are brick-concrete recycled coarse aggregate. The brick-concrete recycled coarse aggregate in the embodiment has a particle size range of 4.75mm~31.5mm, which comes from Xuchang Jinke Recycling Resources Co., Ltd. in Henan Province; Brick-concrete recycled fine aggregate is a granular material with a particle size of less than 4.75 mm obtained from abandoned brick-concrete structure construction waste. It mainly includes crushed bricks, mortar particles and other components. The brick-concrete recycled fine aggregate in the embodiment has a particle size range of 1.18 mm to 4.75 mm, a fineness modulus of 2.62, and is sourced from Xuchang Jinke Recycling Resources Co., Ltd. in Henan Province; Cement, P•O 42.5 grade cement, brand: Tianrui; Polycarboxylic acid high-performance water reducer, model SPF-300, from Liaoning Kelong Fine Chemical Co., Ltd.; End hook steel fiber, diameter: 0.75mm, average length: 35mm, cross section: round, from Hebei Baihang Steel Products Factory; Waterborne polyurethane-epoxy resin emulsion, model 5520-w-60A, brand: American Hexion; Eucommia gum, purity: >96%, brand: Shandong Belon; Nanoclay, particle size: 60nm. Example 1

[0022] A method for preparing fully recycled concrete comprises the following steps: 1188 parts by weight of brick-concrete recycled coarse aggregate and 669 parts by weight of brick-concrete recycled fine aggregate were added into a mixer and mixed for 120 seconds, 530 parts by weight of cement and 106 parts by weight of water were added, and the mixing was continued for 90 seconds; then 106 parts by weight of water and 2.65 parts by weight of polycarboxylic acid high-performance water-reducing agent were added, and the mixing was continued for 60 seconds; then 78 parts by weight of end-hook steel fibers were evenly sprinkled in, mixed for 180 seconds, and discharged to prepare fully recycled concrete. Example 2

[0023] A method for preparing fully recycled concrete comprises the following steps: 1188 parts by weight of brick-concrete recycled coarse aggregate and 669 parts by weight of brick-concrete recycled fine aggregate were added into a mixer and mixed for 120 seconds, 530 parts by weight of cement, 50 parts by weight of reinforcing and toughening agent and 106 parts by weight of water were added, and the mixing was continued for 90 seconds; then 106 parts by weight of water and 2.65 parts by weight of polycarboxylic acid high-performance water-reducing agent were added, and the mixing was continued for 60 seconds; then 78 parts by weight of end hook steel fiber were evenly sprinkled in, stirred for 180 seconds, and discharged to prepare fully recycled concrete.

[0024] The reinforcing and toughening agent is prepared by mixing waterborne polyurethane-epoxy resin emulsion and a synergist in a mass ratio of 3:1.

[0025] The preparation method of the synergist comprises the following steps: S1. Mix 2 parts by weight of eucommia gum with 100 parts by weight of toluene and stir until the eucommia gum is dissolved, then add 0.35 parts by weight of hydrogen peroxide and 0.14 parts by weight of formic acid, and mix and react at 40°C for 5 hours to obtain a mixed solution; then add 10 parts by weight of water to the mixed solution, and continue stirring for 1 hour to obtain an epoxidized eucommia gum latex; mix 10 parts by weight of nanoclay with 100 parts by weight of water and stir to obtain a suspension, then add the suspension to the above-mentioned epoxidized eucommia gum latex, continue stirring and reacting for 1 hour, and the product is precipitated with anhydrous ethanol, washed, and vacuum dried at room temperature to obtain modified nanoclay; S2. Mix 2 parts by weight of the modified nanoclay prepared in the above step S1, 33 parts by weight of anhydrous ethanol and 0.06 parts by weight of phytic acid, and stir at 400 rpm and 82° C. for 4 hours to obtain a mixed solution; centrifuge the mixed solution, collect the precipitate, wash it with water, and then vacuum dry it at 62° C. to obtain a nanoclay composite material, i.e., a synergist. Example 3

[0026] A method for preparing fully recycled concrete, which is different from Example 2 in that the method for preparing the synergist comprises the following steps: S1. Mix 2 parts by weight of eucommia gum with 100 parts by weight of toluene and stir until the eucommia gum is dissolved, then add 0.35 parts by weight of hydrogen peroxide and 0.14 parts by weight of formic acid, and mix and react at 40°C for 5 hours to obtain a mixed solution; then add 10 parts by weight of water to the mixed solution, and continue stirring for 1 hour to obtain an epoxidized eucommia gum latex; mix 10 parts by weight of nanoclay with 100 parts by weight of water and stir to obtain a suspension, then add the suspension to the above-mentioned epoxidized eucommia gum latex, continue stirring and reacting for 1 hour, and the product is precipitated with anhydrous ethanol, washed, and vacuum dried at room temperature to obtain modified nanoclay; S2. Mix 2 parts by weight of the modified nanoclay prepared in the above step S1, 33 parts by weight of anhydrous ethanol, 0.06 parts by weight of phytic acid and 0.03 parts by weight of zinc chloride, and stir at 400 rpm and 82° C. for 4 hours to obtain a mixed solution; centrifuge the mixed solution, collect the precipitate, wash it with water, and then vacuum dry it at 62° C. to obtain a nanoclay composite material, i.e., a synergist. Example 4

[0027] A method for preparing fully recycled concrete, which is different from Example 2 in that the method for preparing the synergist comprises the following steps: S1. Mix 2 parts by weight of eucommia gum with 100 parts by weight of toluene and stir until the eucommia gum is dissolved, then add 0.35 parts by weight of hydrogen peroxide and 0.14 parts by weight of formic acid, and mix and react at 40°C for 5 hours to obtain a mixed solution; then add 10 parts by weight of water to the mixed solution, and continue stirring for 1 hour to obtain an epoxidized eucommia gum latex; mix 10 parts by weight of nanoclay with 100 parts by weight of water and stir to obtain a suspension, then add the suspension to the above-mentioned epoxidized eucommia gum latex, continue stirring and reacting for 1 hour, and the product is precipitated with anhydrous ethanol, washed, and vacuum dried at room temperature to obtain modified nanoclay; S2. Mix 2 parts by weight of the modified nanoclay prepared in the above step S1, 33 parts by weight of anhydrous ethanol, 0.06 parts by weight of phytic acid and 0.03 parts by weight of cerous nitrate hexahydrate, and stir at 400 rpm and 82° C. for 4 hours to obtain a mixed solution; centrifuge the mixed solution, collect the precipitate, wash it with water, and then vacuum dry it at 62° C. to obtain a nanoclay composite material, i.e., a synergist. Comparative Example 1

[0028] A method for preparing fully recycled concrete, which is different from Example 2 in that the method for preparing the synergist comprises the following steps: 2 parts by weight of eucommia gum and 100 parts by weight of toluene are mixed and stirred until the eucommia gum is dissolved, and then 0.35 parts by weight of hydrogen peroxide and 0.14 parts by weight of formic acid are added, and the mixture is mixed and reacted at 40°C for 5 hours to obtain a mixed solution; then 10 parts by weight of water are added to the mixed solution, and the mixture is stirred for 1 hour to obtain an epoxidized eucommia gum latex; 10 parts by weight of nanoclay are mixed and stirred with 100 parts by weight of water to obtain a suspension, and the suspension is added to the above-mentioned epoxidized eucommia gum latex, and the reaction is stirred for 1 hour. The product is precipitated with anhydrous ethanol, washed, and dried in vacuo at room temperature to obtain modified nanoclay, i.e., a synergist. Comparative Example 2

[0029] A method for preparing fully recycled concrete comprises the following steps: 1188 parts by weight of brick-concrete recycled coarse aggregate and 669 parts by weight of brick-concrete recycled fine aggregate were added into a mixer and mixed for 120 seconds, 530 parts by weight of cement, 50 parts by weight of reinforcing and toughening agent and 106 parts by weight of water were added, and the mixing was continued for 90 seconds; then 106 parts by weight of water and 2.65 parts by weight of polycarboxylic acid high-performance water-reducing agent were added, and the mixing was continued for 60 seconds; then 78 parts by weight of end hook steel fiber were evenly sprinkled in, stirred for 180 seconds, and discharged to prepare fully recycled concrete.

[0030] The reinforcing and toughening agent is prepared by mixing waterborne polyurethane-epoxy resin emulsion and nano-clay in a mass ratio of 3:1. Comparative Example 3

[0031] A method for preparing fully recycled concrete comprises the following steps: 1188 parts by weight of brick-concrete recycled coarse aggregate and 669 parts by weight of brick-concrete recycled fine aggregate were added into a mixer and mixed for 120 seconds, 530 parts by weight of cement, 50 parts by weight of reinforcing and toughening agent and 106 parts by weight of water were added, and the mixing was continued for 90 seconds; then 106 parts by weight of water and 2.65 parts by weight of polycarboxylic acid high-performance water-reducing agent were added, and the mixing was continued for 60 seconds; then 78 parts by weight of end hook steel fiber were evenly sprinkled in, stirred for 180 seconds, and discharged to prepare fully recycled concrete.

[0032] The reinforcing and toughening agent is waterborne polyurethane-epoxy resin emulsion. Test Example 1

[0033] Heyi performance and mechanical properties testing Slump is one of the important indicators for measuring the workability of fresh concrete mixtures. Therefore, the present invention tests the workability of concrete by testing the slump of each embodiment and comparative example; the slump test is carried out in accordance with GB / T 50080-2016 Standard for Test Methods for Properties of Ordinary Concrete Mixtures; Compressive strength, splitting tensile strength and axial tensile strength are important mechanical property indicators of concrete mixtures. They play a vital role in evaluating the quality and performance of concrete, and are of great significance for ensuring the safety and durability of concrete structures. Therefore, the present invention tests the mechanical properties of concrete by testing the compressive strength, splitting tensile strength and axial tensile strength of each embodiment and comparative example. The compressive strength and splitting tensile strength tests were carried out with reference to the "GB / T 50081-2019 Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the test instrument used was a YAW-3000 microcomputer-controlled constant loading pressure testing machine; the axial tensile strength test was carried out with reference to the "GB / T 50081-2019 Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the test instrument used was a WAW-600D microcomputer-controlled universal pressure testing machine; The specific test results are shown in Table 1 below: Table 1

[0034] As shown in Table 1, by comparing Examples 1-4 and Comparative Examples 1-3, it is found that compared with Example 1, the slump of Examples 2-4 and Comparative Examples 1-3, which are added with reinforcing and toughening agents, is reduced, and the downward trend of Examples 2-4 and Comparative Example 1 is relatively small, while the downward trend of Comparative Examples 2-3 is obvious, among which the downward trend of Comparative Example 3 is the most obvious. The reason may be that the addition of waterborne polyurethane-epoxy resin emulsion increases the viscosity of concrete, resulting in a decrease in slump, while the introduction of the synergist nanoclay composite material can form a network structure, which may improve the rheological properties of concrete and reduce the free flow of water, thereby alleviating the downward trend of slump.

[0035] By comparing Examples 1-4 and Comparative Examples 1-3, it is found that the compressive strength, splitting tensile strength, and axial tensile strength of Examples 2-4 are significantly higher than those of Examples 1 and Comparative Examples 1-3, among which the compressive strength, splitting tensile strength, and axial tensile strength of Example 4 are the highest, indicating that the reinforcing and toughening agent prepared by mixing the nanoclay composite material as a synergist with the waterborne polyurethane-epoxy resin emulsion is beneficial to improving the compressive strength, splitting tensile strength, and axial tensile strength of concrete, and is beneficial to improving the mechanical properties of concrete. The reason may be that the introduction of epoxidized eucommia gum and phytic acid in the nanoclay composite material increases the surface activity of the nanoclay, making it better dispersed in the concrete to form a uniform reinforcement phase, and the nanoclay composite material can form a uniformly distributed cross-linked network structure with the polymer in the waterborne polyurethane-epoxy resin emulsion, further enhancing the microstructure of the concrete. Therefore, the synergistic use of the nanoclay composite material and the waterborne polyurethane-epoxy resin emulsion can not only effectively disperse stress and improve the density and strength of the concrete, but also improve the toughness and crack resistance of the concrete, reduce the generation and expansion of microcracks, and help improve the tensile properties of the concrete. In addition, the nanoclay composite material can improve the interface transition zone in the concrete, improve the bonding force between the aggregate and the cement stone, and thus improve the overall performance of the concrete.

[0036] Comparing Example 3 and Example 4, it is found that the mechanical properties of Example 4 are better than those of Example 3. The reason may be that the corrosion inhibitor used in the preparation of the synergist in Example 3 is zinc chloride, while the corrosion inhibitor used in Example 4 is cerous nitrate hexahydrate. 2+ ), cerium ion (Ce 3+ ) has a large coordination number and strong coordination ability, and can form stable coordination compounds with multiple phosphate groups in phytic acid. This coordination effect not only enhances the chemical stability of the nanoclay surface, enabling it to remain stable in the alkaline environment of concrete, but also makes it less susceptible to hydrolysis or ion exchange, thus being more conducive to improving the mechanical properties of concrete. Test Example 2

[0037] Chloride ion penetration resistance test Chloride ion penetration resistance is one of the main research contents of concrete impermeability durability. The difficulty of gas, liquid and ion entering the concrete under the influence of external environment can reflect the strength of concrete anti-penetration performance. Chloride ions enter the concrete through molecular movement caused by the difference in chloride ion concentration inside and outside the concrete specimen. It is generally expressed by the chloride ion diffusion coefficient. The larger the chloride ion diffusion coefficient, the worse the chloride ion penetration resistance.

[0038] According to GB / T 50082-2009 Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete, the rapid chloride ion migration coefficient method (RCM method) was used to conduct the chloride ion penetration test. The specimen was a cylindrical specimen with a size of φ100×50mm. The chloride ion diffusion coefficient D was calculated based on the test results. RCM , and according to the chloride ion diffusion coefficient D of concrete of each embodiment and comparative example RCM The chloride ion penetration resistance of concrete is evaluated. The evaluation method of the chloride ion penetration resistance of concrete refers to the chloride ion diffusion coefficient standard in Table 2 below: Table 2 Chloride ion diffusion coefficient standard

[0039] The specific test results are shown in Table 3 below: Table 3

[0040] As shown in Table 3, by comparing Examples 1-4 with Comparative Examples 1-3, it is found that compared with Example 1, the chloride ion diffusion coefficients of Examples 2-4 and Comparative Examples 1-3 are decreased, indicating that the introduction of the reinforcing toughening agent is beneficial to improving the chloride ion penetration resistance of concrete. By comparing Examples 2-4 with Comparative Examples 1-3, it is found that the chloride ion diffusion coefficient of Example 2-4 is significantly lower than that of Comparative Examples 1-3, and the chloride ion penetration resistance is evaluated as "good", among which the chloride ion diffusion coefficient of Example 4 is the lowest, indicating that the reinforcing toughening agent prepared by mixing the nano-clay composite material as a synergist with the waterborne polyurethane-epoxy resin emulsion is beneficial to improving the chloride ion penetration resistance of concrete. The possible reason is that the nanoclay composite material is added to the waterborne polyurethane-epoxy resin emulsion. Due to the large specific surface area and layered structure of the nanoclay and the presence of epoxy eucommia gum and phytic acid grafted on its surface, it can be evenly distributed in the waterborne polyurethane-epoxy resin emulsion and form a dense cross-linked network structure, forming a uniform protective barrier to prevent the penetration of chloride ions. At the same time, due to the coordination effect of the corrosion-inhibiting ions in the nanoclay composite material, the stability of this barrier is further enhanced, making it more difficult for chloride ions to migrate and diffuse inside the concrete, thereby stably improving the concrete's resistance to chloride ion penetration. At the same time, the phosphate groups in the phytic acid on the surface of the nanoclay composite material and the corrosion-inhibiting ions such as zinc ions (Zn 2+ ) or cerium ions (Ce 3+ ) can form stable chemical bonds with chloride ions, forming a chemical barrier, which can further prevent the penetration of chloride ions.

[0041] Comparing Example 3 and Example 4, it is found that the anti-chloride ion penetration performance of Example 4 is better than that of Example 3. The reason may be that the corrosion inhibitor used in the preparation process of the synergist in Example 3 is zinc chloride, while the corrosion inhibitor used in Example 4 is cerous nitrate hexahydrate. 2+ ), cerium ion (Ce 3+ ) has a large coordination number and strong coordination ability, and can form stable coordination compounds with multiple phosphate groups in phytic acid. This coordination effect not only enhances the chemical stability of the nanoclay surface, enabling it to remain stable in the alkaline environment of concrete and not easily hydrolyzed or ion exchanged, thereby effectively preventing the penetration of chloride ions for a long time, but also can form a denser chemical barrier to more effectively prevent the penetration of chloride ions. Test Example 3

[0042] Freeze-thaw cycle test Referring to GB / T 50082-2009 Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete, the freeze-thaw cycle test was carried out using the quick freezing method. The specimen size was 100 mm×100 mm×400 mm for prism specimens and 100 mm×100 mm×100 mm for cube specimens. The freeze-thaw cycle test was carried out using a walk-in multifunctional environmental simulation test system. The number of freeze-thaw cycles was designed to be 100 times. The mass and dynamic elastic modulus of the prism specimens were measured every 50 freeze-thaw cycles, and the mass loss rate and relative dynamic elastic modulus loss were calculated; the compressive strength of the cube specimens was tested every 50 freeze-thaw cycles, and the strength loss was calculated; The specific test results are shown in Table 4 below: Table 4

[0043] As shown in Table 4, by comparing Examples 1-4 and Comparative Examples 1-3, it is found that the mass loss rate and compressive strength loss rate of Examples 2-4 after 50 and 100 freeze-thaw cycles are significantly lower than those of Examples 1 and Comparative Examples 1-3, and the relative dynamic elastic modulus is significantly higher than that of Examples 1 and Comparative Examples 1-3, wherein the mass loss rate and compressive strength loss rate of Example 4 after 50 and 100 freeze-thaw cycles are the lowest, and the relative dynamic elastic modulus is the highest; it is shown that the use of nano-clay composite materials as synergists and waterborne polyurethane-epoxy resin emulsions to prepare the reinforcing toughening agent is beneficial to improving the freeze-thaw resistance of concrete. The reason for the analysis may be that the introduction of epoxidized eucommia gum and phytic acid in the nano-clay composite material increases the surface activity of the nano-clay, so that it is better dispersed in the concrete, forming a uniform reinforcing phase, improving the microstructure of the concrete, reducing the internal porosity, and improving the density and durability of the concrete, thereby improving the freeze-thaw resistance of the concrete, and the coordination effect of the corrosion-inhibiting ions further enhances the stability of this reinforcing phase, which is beneficial to further improve the freeze-thaw resistance of the concrete. Nanoclay composite materials are used in conjunction with waterborne polyurethane-epoxy resin emulsion. The interaction between the two can form a physical and chemical dual barrier in concrete, jointly improve the interface transition zone between aggregate and cement stone, enhance the bonding strength and durability of the interface, and thus significantly improve the freeze-thaw resistance of concrete.

[0044] Comparing Example 3 and Example 4, it is found that the freeze-thaw resistance of Example 4 is better than that of Example 3. The reason may be that the corrosion inhibitor used in the preparation of the synergist in Example 3 is zinc chloride, while the corrosion inhibitor used in Example 4 is cerous nitrate hexahydrate. 2+ ), cerium ion (Ce 3+) has higher chemical stability and can remain stable in the alkaline environment of concrete. It is not easily hydrolyzed or ion exchanged. This stability helps to maintain the structural integrity of the nanoclay composite material during the freeze-thaw cycle and reduce the generation of microcracks caused by chemical changes. 2+ ) The coordination compound formed is relatively unstable in an alkaline environment and is prone to hydrolysis or ion exchange, resulting in the gradual failure of the chemical barrier, which makes it easier to generate microcracks during the freeze-thaw cycle. Therefore, Example 4 has a stronger freeze-thaw resistance.

Claims

1. A method for preparing fully recycled concrete, characterized in that: The following steps are involved: Add brick-concrete recycled coarse aggregate and brick-concrete recycled fine aggregate into a mixer and mix and stir for 110-130s, add cement and water accounting for 1 / 2 of the total mass of water, and continue to stir for 80-100s; then add the remaining 1 / 2 of water and polycarboxylic acid high-performance water reducer, and continue to stir for 50-70s; then evenly sprinkle steel fiber, stir for 160-200s, and discharge the material to prepare fully recycled concrete; the weight ratio of each raw material component is: 290-540 parts of cement, 1100-1200 parts of brick-concrete recycled coarse aggregate, 650-680 parts of brick-concrete recycled fine aggregate, 145-250 parts of water, 30-80 parts of steel fiber, and 1.4-2.7 parts of polycarboxylic acid high-performance water reducer; Alternatively, brick-concrete recycled coarse aggregate and brick-concrete recycled fine aggregate are added to a mixer and mixed for 110-130 seconds, cement, reinforcing and toughening agent and water accounting for 1 / 2 of the total mass of water are added, and stirring is continued for 80-100 seconds; then the remaining 1 / 2 of the water and polycarboxylic acid high-performance water reducer are added, and stirring is continued for 50-70 seconds; then steel fiber is evenly sprinkled, stirred for 160-200 seconds, and the material is discharged to prepare fully recycled concrete; the weight ratio of each raw material component is: 290-540 parts of cement, 1100-1200 parts of brick-concrete recycled coarse aggregate, 650-680 parts of brick-concrete recycled fine aggregate, 145-250 parts of water, 30-80 parts of steel fiber, 1.4-2.7 parts of polycarboxylic acid high-performance water reducer, and 40-60 parts of reinforcing and toughening agent.

2. The method for preparing fully recycled concrete according to claim 1, characterized in that: The steel fiber is selected from one of a corrugated steel fiber and an end hook steel fiber.

3. The method for preparing fully recycled concrete according to claim 1, characterized in that: The reinforcing and toughening agent is prepared by mixing waterborne polyurethane-epoxy resin emulsion and a synergist in a mass ratio of 2-4:

1.

4. The method for preparing fully recycled concrete according to claim 3, characterized in that: The preparation method of the synergist comprises the following steps, calculated by weight: S1, 1.5-3 parts by weight of eucommia gum and 95-105 parts by weight of toluene are mixed and stirred until the eucommia gum is dissolved, and then 0.3-0.4 parts by weight of hydrogen peroxide and 0.1-0.2 parts by weight of formic acid are added, and the mixture is reacted at 38-42° C. for 4-6 hours to obtain a mixed solution; then 8-12 parts by weight of water are added to the mixed solution, and the mixture is stirred for 0.5-2 hours to obtain an epoxidized eucommia gum latex; 8-12 parts by weight of nanoclay are mixed and stirred with 95-105 parts by weight of water to obtain a suspension, and the suspension is added to the above-mentioned epoxidized eucommia gum latex, and the reaction is stirred for 0.5-2 hours, and the product is precipitated with anhydrous ethanol, washed, and dried in vacuo at room temperature to obtain modified nanoclay; S2. Mix 1.5-3 parts of the modified nanoclay prepared in the above step S1, 25-35 parts of anhydrous ethanol and 0.01-0.1 parts of phytic acid, and stir at 300-500 rpm and 75-85° C. for 3-5 hours to obtain a mixed solution; centrifuge the mixed solution, collect the precipitate, wash it with water, and then vacuum dry it at 55-65° C. to obtain a nanoclay composite material, i.e., a synergist.

5. The method for preparing fully recycled concrete according to claim 4, characterized in that: The step S2 may also be, by weight: 1.5-3 parts of the modified nanoclay prepared in the above step S1, 25-35 parts of anhydrous ethanol, 0.01-0.1 parts of phytic acid and 0.01-0.05 parts of a corrosion inhibitor are mixed, and the mixture is stirred at 300-500 rpm and 75-85° C. for 3-5 hours to obtain a mixed solution; the mixed solution is centrifuged, the precipitate is collected, and the precipitate is washed with water and vacuum dried at 55-65° C. to obtain a nanoclay composite material, i.e., a synergist.

6. The method for preparing fully recycled concrete according to claim 5, characterized in that: The corrosion inhibitor is selected from at least one of zinc chloride and cerous nitrate hexahydrate.

7. A fully recycled concrete, characterized in that: Prepared by the method according to any one of claims 1 to 6.

8. Use of the fully recycled concrete as claimed in claim 7 in bridges, roads and high-rise buildings.

Citation Information

Patent Citations

  • Environment-friendly concrete and preparation method thereof

    CN111320438A

  • Preparation method of epoxidated-gutta-percha-toughened polylactic acid

    CN106280340A

  • Micro-expansive epoxy emulsion modified self-compacting concrete for composite lining structure

    CN112608122A

  • Waterproof anti-seepage medium-high-strength resin concrete for underground space and preparation process of waterproof anti-seepage medium-high-strength resin concrete

    CN114426422A

  • High-strength compression-resistant crack-resistant lightweight aggregate concrete and preparation method thereof

    CN116789411A